Osteoarthritis-associated basic calcium phosphate crystals activate membrane proximal kinases in human innate immune cells. Issue 1 (December 2017) - Corr, Emma; Cunningham, Clare; Helbert, Laura; McCarthy, Geraldine; Dunne, Aisling
Abstract Background Osteoarthritis (OA) is a chronic debilitating joint disorder of particularly high prevalence in the elderly population. Intra-articular basic calcium phosphate (BCP) crystals are present in the majority of OA joints and are associated with severe degeneration. They are known to activate macrophages, synovial fibroblasts, and articular chondrocytes, resulting in increased cell proliferation and the production of pro-inflammatory cytokines and matrix metalloproteases (MMPs). This suggests a pathogenic role in OA by causing extracellular matrix degradation and subchondral bone remodelling. There are currently no disease-modifying drugs available for crystal-associated OA; hence, the aim of this study was to explore the inflammatory pathways activated by BCP crystals in order to identify potential therapeutic targets to limit crystal-induced inflammation. Methods Primary human macrophages and dendritic cells were stimulated with BCP crystals, and activation of spleen tyrosine kinase (Syk), phosphoinositide-3 kinase (PI3K), and mitogen-activated protein kinases (MAPKs) was detected by immunoblotting. Lipopolysaccharide (LPS)-primed macrophages were pre-treated with inhibitors of Syk, PI3K, and MAPKs prior to BCP stimulation, and cytokine production was quantified by enzyme-linked immunosorbent assay (ELISA). Aa an alternative, cells were treated with synovial fluid derived from osteoarthritic knees in the presence or absence of BCP crystals, and gene induction was assessed by real-time polymerase chain reaction (PCR). Results We demonstrate that exposure of primary human macrophages and dendritic cells to BCP crystals leads to activation of the membrane-proximal tyrosine kinases Syk and PI3K. Furthermore, we show that production of the pro-inflammatory cytokines interleukin (IL)-1α and IL-1β and phosphorylation of downstream MEK and ERK MAPKs is suppressed following treatment with inhibitors of Syk or PI3K. Finally, we demonstrate that treatment of macrophages with BCP crystals induces the production of the damage-associated molecule S100A8 and MMP1 in a Syk-dependent manner and that synovial fluid from OA patients together with BCP crystals exacerbates these effects. Conclusions We identify Syk and PI3K as key signalling molecules activated by BCP crystals prior to inflammatory cytokine and DAMP expression and therefore propose that Syk and PI3K represent potential targets for the treatment of BCP-related pathologies.